2003
DOI: 10.1046/j.1440-172x.2003.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Risks for unplanned hospital readmission in a teaching hospital in southern Taiwan

Abstract: The purpose of this study was to assess and analyse hospital readmission and its risk factors for patients who were visited by a discharge planning coordinator during hospitalization in a teaching hospital located in southern Taiwan. Results found that 67 patients (5.7%) were readmitted within 14 days of discharge during the data collection period. Twenty-eight patients (41.8%) were readmitted because of complications. Patients' previous diagnoses and complications were two major reasons for patients to be re-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Räty et al 2003). It has been reported that home-care clients use a lot of other services, in addition to home care, such as visits to doctors and to the emergency department, as well as periods in institutions (Andersson et al 2005;Smith et al 2005;Furhoff 2002, 2004;Chang et al 2003). According to Noro et al (1999), women were more likely to use health-care services, but their share of total expenditure was lower than that of men.…”
Section: Introductionmentioning
confidence: 99%
“…Räty et al 2003). It has been reported that home-care clients use a lot of other services, in addition to home care, such as visits to doctors and to the emergency department, as well as periods in institutions (Andersson et al 2005;Smith et al 2005;Furhoff 2002, 2004;Chang et al 2003). According to Noro et al (1999), women were more likely to use health-care services, but their share of total expenditure was lower than that of men.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] For these patients, we collected from the outpatient medical record the number of PCP telephone contacts over the first 7 days following discharge. We ascertained time from index hospitalization until death from the Social Security Death Index (SSDI).…”
Section: Data Collection and Measuresmentioning
confidence: 99%
“…Chang et al [9] Descriptive, Retrospective (Level VI) [29] Observational Pilot (Level VI) 118 PTs from a RCT were evaluated for progress of study. Intervention involved implementation of care management program for "at-risk" older adults.…”
Section: Xmentioning
confidence: 99%
“…No differences in unplanned readmissions were noted. The second study [9] , a retrospective, descriptive study, analyzed 14-day readmission and risk factor data for patients who were visited by a discharge planning coordinator during hospitalization. The 14-day unplanned readmission rate was significantly greater for patients visited by social workers, home-care nurses, and hospice home-care nurses (p < .05) versus other types of health care providers (e.g., physical therapists, nutritionists, and diabetes education specialists).…”
Section: Intervention During Hospitalizationmentioning
confidence: 99%